High-Intensity Interval Training Attenuates Insulin Resistance Induced by Sleep Deprivation in Healthy Males - de Souza, Jorge F. T.; Dáttilo, Murilo; de Mello, Marco T.; Tufik, Sergio; Antunes, Hanna K. M. (Frontiers in Physiology, 2017)
Introduction: Sleep deprivation can impair several physiological systems and recently, new evidence has pointed to the relationship between a lack of sleep and carbohydrate metabolism, consequently resulting in insulin resistance. To minimize this effect, High-Intensity Interval Training (HIIT) is emerging as a potential strategy. Objective: The aim of this study was to investigate the effects of HIIT on insulin resistance induced by sleep deprivation. Method: 11 healthy male volunteers were recruited, aged 18-35 years, who declared taking 7-8 h sleep per night. All volunteers were submitted to four different conditions: a single night of regular sleep (RS condition), 24 hours of total sleep deprivation (SD condition), HIIT training followed by regular sleep (HIIT+RS condition), and HIIT training followed by 24 hours of total sleep deprivation (HIIT+SD condition). They performed six training sessions over 2 weeks and each session consisted of 8-12 x 60s intervals at 100% of peak power output. In each experimental condition, tests for glucose, insulin, cortisol, free fatty acids, and insulin sensitivity, measured by oral glucose tolerance test (OGTT), were performed. Results: Sleep deprivation increased glycaemia and insulin levels, as well as the area under the curve. Furthermore, an increase in free fatty acids concentrations and basal metabolism was observed. There were no differences in the concentrations of cortisol. However, HIIT before 24 hours of sleep deprivation attenuated the increase of glucose, insulin and free fatty acids. Conclusion: 24 hours of sleep deprivation resulted in acute insulin resistance. However, HIIT is an effective strategy to minimize the deleterious effects promoted by this condition.